La calidad del servicio educativo y atención de los centros infantiles del buen vivir, perspectiva y expectativas de los padres de familia, estudio de caso en el CIBV “Kuri Sisa” - Catucuago Cuascota, Nancy Beatriz (2014)
This research work was conducted at the CIBV "Kuri Sisa" the Chaupiloma community, canton Pedro Moncayo, parish Tupigachi; This was done with the participation of teachers, parents and mothers of the institution and the community. It was necessary to analyze the quality of education and care of children's centers of Good Living from the perspective and expectations of parents; taking into account that early childhood is considered the primary stage in human life, where the development of skills and abilities is power. For this we have taken into account the various theories of development proposed by several authors who have submitted their research, among the highlights are: Piaget, Vygotsky, Ausubel, Dewey, Montessori. Based on these investigations the development of early childhood also addressed from the cultural, spiritual and ancestral rescuing community values.